Analisis Peraturan Menteri Pembangunan Umum dan Perumahan Rakyat No. 1 Tahun 2017 Tentang Tata Cara Pelaksanaan Pengadaaan Badan Usaha Untuk Pengusahaan Jalan Tol Terhadap Prinsip Persaingan Usaha Yang Sehat - Zunov, Farahannesa; Sukarmi; Alam, Moch. Zairul (Faculty of Law, Universitas Brawijaya, 2022)
This research aims to analyze the implementation of fair business competition in the provision of Regulation of the Minister of Public and Housing Development Number 1 of 2017 concerning the Procedures of the Procurement of Legal Entity in a Highway Toll Project (henceforth referred to as Ministerial Regulation) by analyzing the implementation of fair business competition principle in an auction service of a business entity as governed in the Ministerial Regulation and the provision of the agreement regarding the highway toll project procurement that may take up to 50 years, and this period can be extended. However, there have not been any standards of business entity in terms of how this agreement is extended and any standards that set the maximum period of the extension. That is, this research investigates whether the extension period without any strict deadline complies with the substantive aspect of Law Number 5 of 1999 concerning the Ban on Monopolistic and Unfair Business Competition Practices.